in Digital Logic
150 views
0 votes
0 votes

Reduce this Boolean Expression to one literal

$$\bar W X( \bar Z +\bar YZ ) + X( W+\bar WYZ)$$

  1. $W$
  2. $Z$
  3. $X$
  4. $Y$
in Digital Logic
by
150 views

3 Answers

1 vote
1 vote
Answer : C.
We can use the Kornaugh map as the it is the sum of Product of terms
(4,5,6,7,12,13,14,15) so it came out to be = X.
1 vote
1 vote
F = w'x(z' + y'z) + x(w + w'yz)

  = w'x(z' + y')(z' + z) + x(w +w')(w + yz)

  = w'x(z' + y') + x(w + yz)

  = x(w'z' + w'y' + w + yz)

  = x((w +w')(w + z') + w'y' + yz)

  = x(w + z' + w'y' +yz)

  = x((w + w')(w + y') + (z' +y)(z' + z))

  = x(w + y' + z' + y)

  = x(w + z' + 1)

  = x*1

  = x
by
0 votes
0 votes

Answer : C

Convert expression into minterms : m(8,9,10,12,13,15) and using k map Final expression is X.

k map expression is 

 = XW' + XYZ + XY'Z'

 = XW' + X

= X 

Answer:

Related questions